CINTA TANAH AIR DALAM PERSPEKTIF PARTAI POLITIK - Harry Safari Margapradja (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2018)
The homeland is a strong nature and becomes the character of every human being.Separating from the homeland or even the hometown feels heavy and tormenting. In Tafsiral-Kabir, Juz XV, p. 165; al-Imam Fakhr Al-Din al-Razi said that;